Novel TCR-based biologics: mobilising T cells to warm 'cold' tumours. (July 2019) - Lowe, Kate L.; Cole, David; Kenefeck, Rupert; OKelly, Ita; Lepore, Marco; Jakobsen, Bent K.
Highlights: Novel strategies to treat immunologically 'cold' or low mutation tumours are urgently needed. TCR-based therapeutics can target a broader range of tumour antigens. Soluble T cell redirectors bypass challenges associated with adoptive cell therapies. Tebentafusp (IMCgp100) has shown clinical efficacy in patients with uveal melanoma. Abstract: Immunotherapeutic strategies have revolutionised cancer therapy in recent years, bringing meaningful improvements in outcomes for patients with previously intractable conditions. These successes have, however, been largely limited to certain types of liquid tumours and a small subset of solid tumours that are known to be particularly immunogenic. Broadening these advances across the majority of tumour indications, which are characterised by an immune-excluded, immune-deserted or immune-suppressed ('cold') phenotype, will require alternative approaches that are able to specifically address this unique biological environment. Several newer therapeutic modalities, including adoptive cell therapy and T cell redirecting bispecific molecules, are considered to hold particular promise and are being investigated in early phase clinical trials across various solid tumour indications. ImmTAC molecules are a novel class of T cell redirecting bispecific biologics that exploit TCR-based targeting of tumour cells; providing potent and highly specific access to the vast landscape of intracellular targets. The first of these reagents to reach the clinic, tebentafusp (IMCgp100), has generated demonstrable clinical efficacy in an immunologically cold solid tumour with a high unmet need. Here, we highlight the key elements of the ImmTAC platform that make it ideally positioned to overcome the cold tumour microenvironment in an off-the-shelf format.